Genetic resources as initial material for developing new soft winter wheat varieties - В. М. Кір’ян; М. В. Кір’ян; Р. С. Вискуб (Plant Varieties Studying and Protection)
Purpose. To estimate genetic resources collection of soft winter wheat plants (new collection accessions) of Ustymivka Experimental Station for Plant Production and select initial material for breeding of adaptive, productive and qualitative soft winter wheat varieties.